2023
DOI: 10.3390/medicina59050919
|View full text |Cite
|
Sign up to set email alerts
|

Supplement Consumption and Periodontal Health: An Exploratory Survey Using the BigMouth Repository

Abstract: Background: Dietary supplements have been investigated for their impact on the periodontal apparatus (alveolar bone, mucosa, periodontal ligament, and cementum) and their hypothetical protective role against periodontitis. There remains a gap in the field in this area. Thus, the present study aims to examine the correlation between populations who report taking different dietary supplements and their relative periodontal health. Methods: The BigMouth dental data repository derived from the dental Electronic He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Similar to our findings, the Mendelian randomization study of Liao et al also failed to show a strong association between coffee-consuming behavior and periodontitis, indicating a risk increase of ~1% [ 55 ]. The study of Saleh et al established the role of regular vitamin and supplement consumption on periodontal health in adults, using the “BigMouth” dental data repository: among the 21 supplements surveyed, only the consumption of multivitamins and iron showed substantial benefits for periodontal health [ 56 ]. Furthermore, the role of vitamin D in the maintenance of periodontal health—both in the context of bone metabolism and as an anti-inflammatory agent—was described [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, the Mendelian randomization study of Liao et al also failed to show a strong association between coffee-consuming behavior and periodontitis, indicating a risk increase of ~1% [ 55 ]. The study of Saleh et al established the role of regular vitamin and supplement consumption on periodontal health in adults, using the “BigMouth” dental data repository: among the 21 supplements surveyed, only the consumption of multivitamins and iron showed substantial benefits for periodontal health [ 56 ]. Furthermore, the role of vitamin D in the maintenance of periodontal health—both in the context of bone metabolism and as an anti-inflammatory agent—was described [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between folate and periodontitis is still somewhat controversial. In a recent dataset survey (Using the Big Mouth Repository), folate supplementation favored the development of periodontitis 17 . In addition, some scholars have shown that folate receptor (FOLR1) does not appear to have a role in the detection of periodontal disease 10 .…”
Section: Introductionmentioning
confidence: 99%